2023
DOI: 10.1002/mrm.29987
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating slice cross‐talk in multi‐slice multi‐echo spin echo T2 mapping

Ekaterina A. Brui,
Zilya Badrieva,
Charles‐Alexis de Mayenne
et al.

Abstract: PurposeTo investigate whether a T2 inter‐slice variation could occur when a multi‐slice multi‐echo spin echo (MESE) sequence is used for image acquisition and to propose an enhanced method for reconstructing T2 maps that can effectively address and correct these variations.MethodsBloch simulations were performed accounting for the direct saturation effect to evaluate magnetization changes in multi‐slice 2D MESE sequence. Experimental phantom scans were performed to validate these simulations. An improved versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, we assessed the in uence of multi-slice mode on T2 variation among slices. Such a variation has been previously investigated for T2 maps reconstructed from MESE images using dictionary tting [13]. Accordingly, we showed that T2 inter-slice variation was small when 100% slice gaps were utilized (CV < 1%).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In addition, we assessed the in uence of multi-slice mode on T2 variation among slices. Such a variation has been previously investigated for T2 maps reconstructed from MESE images using dictionary tting [13]. Accordingly, we showed that T2 inter-slice variation was small when 100% slice gaps were utilized (CV < 1%).…”
Section: Discussionmentioning
confidence: 64%
“…In order to double-check the T2 values, a "gold-standard" T2 single slice mapping was computed from MR images acquired using a spin echo pulse sequence with the following parameters: TR/TEs = 5.5 s / 10-30-50-100-150-200-300 ms, voxel size = 1.17x1.17x2 mm. In order to assess the effect of a multi-slice ME-TSE acquisition on the inter-slice T2 values homogeneity, single-slice and multi-slice images of the phantoms were obtained using an ME-TSE sequence with the following parameters: TR = 2 s, rst TE = 10.3 ms, inter-echo time = 10.3 ms, turbo factor = 3, number of contrasts = 3, slice thickness = 2 mm, number of slices = 5, inter-slice gap = 0 and 100% (100% gap was used for reference T2 maps, as this gap provides negligible direct saturation between slices [13]). For a ME-TSE acquisition, the k-space for each image is lled with data from different echo times and the number of such echoes is called turbo-factor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations